Surgical Treatment of Jacob’s Disease: A Case Report Involving an Osteochondroma of the Coronoid Process - Dale E. Stringer; Kourt B. Chatelain; Rahul Tandon (Case Reports in Surgery)
Although it is one of the most common benign tumors of bone in the axial skeleton, the osteochondroma is relatively rare in the maxillofacial region. Its discovery on the coronoid process is even more rare. First described by Jacob in 1899, it remains a rare entity as only a few reported cases have been described in the literature. Nevertheless, the symptomatic features remain relatively nonspecific: limited opening, tightness, and slight expansion of the affected area with or without pain. The demographic features are more established, as it affects younger males. Definitive diagnosis is made after histological analysis, post-resection of the growth. We report a 27 year-old male with a history of limited opening and tightness of the mouth. Computed Tomography (CT) imaging revealed a well corticated exophytic protuberance from the left coronoid process. Left coronoidectomy and excision of the exophytic growth was performed, and was confirmed by histologic analysis to be an osteochondroma, demonstrating Jacob’s disease.